Improving concentration skills / Mike Lake and Marjorie Needham. - Lake, Mike (Questions, 2000)
Some children are unable to focus on anything for more than a few seconds; but many can pay attention to a noisy cartoon. To help to define the nature of children's attention problems this work offers a programme for working with children individually